Kurikulum Anti-Radikalisme dalam Pendidikan Pesantren - Badrul Arifin (JURNAL PUSAKA, 2020)
The phenomenon of pesantren radicalism is something novel which recently happened. Islamic boarding schools as religious institutions are not actually established to be the source of radicalism. The pesantren has responsibility to produce knowledgeable religious characters or tafaqquh fi al-din. Therefore, pesantren teaches everything that exists in religion, from Tauhid, Syariah, and also morals. The pesantren development so far, with the intellectual capital that has been maintained by the pesantren, proves for making significant contribution to the formation and development of moderate diversity tone. In the diverse landscape of Muslim societies, pesantren are generators of moderate Islamic ideology, even though the degree of modernism is not explicitly affirmed in the texts of the yellow book (Kitab Kuning). Thus, the pesantren curriculum in itself has proven to be sufficient in the formation of the Islamic entity rãhmatan lil álamin. Keywords: Pesantren, curriculum, radicalism, moderate.